Biomarker geochemistry of Eq34-10 cyclothem shale in Qianjiang Depression of the Jianghan salt lake facies Basin. (17th January 2018) - Wang, Zixiang; Zheng, Youheng; Chen, Fengling; Xie, Xinong; Wu, Shiqiang; Sun, Lina
ABSTRACT: The objective of this study is to provide biomarker geochemistry information on shale between sheet-like salts from Qianjiang Depression of the Jianghan salt lake facies Basin, and illustrate the depositional conditions, source organic matter input and maturation. 7 shale samples from Eq3 4 -10 rhythmic were analysed with gas chromatography-mass spectrometry. The investigated biomarkers show that the shale oil are charactertized by an apperent odd-even preference of n-alkane, low Pr/Ph values and a high content of gammacerane and C30 + hopanes, maderate C21- /C21+ ratios, the high relative content of C27 5α(H), 14α(H), 17α(H)- steranes (20R), and an anomaly high C29 sterane ββ/(ββ + αα) value. These biomarker geochemistry characterizations suggested that the shale oils were derived from mixed aquatic organisms and land plants, and deposited in an anoxic and saline-hypersaline depositional environment.